Digital Manipulation of Images of Models' Appearance in Advertising: Strategies for Action Through Law and Corporate Social Responsibility Incentives to Protect Public Health. Issue 1 (March 2019) - McBride, Caitlin; Costello, Nancy; Ambwani, Suman; Wilhite, Breanne; Austin, S. Bryn
Context: Widespread digital retouching of advertising imagery in the fashion, beauty, and other consumer industries promotes unrealistic beauty standards that have harmful effects on public health. In particular, exposure to misleading beauty imagery is linked with greater body dissatisfaction, worse mood, poorer self-esteem, and increased risk for disordered eating behaviors. Moreover, given the social, psychological, medical, and economic burden of eating disorders, there is an urgent need to address environmental risk factors and to scale up prevention efforts by increasing the regulation of digitally altered advertising imagery. Methods: This manuscript summarizes the health research literature linking digital retouching of advertising to increased risk of eating disorders, disordered weight and appearance control behaviors, and body dissatisfaction in consumers, followed by a review of global policy initiatives designed to regulate digital retouching to reduce health harms to consumers. Next, we turn to the US legal context, reporting on findings generated through legal research via Westlaw and LexisNexis, congressional records, federal agency websites, law review articles, and Supreme Court opinions, in addition to consulting legal experts on both tax law and the First Amendment, to evaluate the viability of various policy initiatives proposed to strengthen regulation on digital retouching in the United States. Findings: Influencing advertising practices via tax incentives combined with corporate social responsibility initiatives may be the most constitutionally feasible options for the US legal context to reduce the use of digitally alternated images of models' bodies in advertising. Conclusions: Policy and corporate initiatives to curtail use of digitally altered images found to be harmful to mental and behavioral health of consumers could reduce the burden of eating disorders, disordered weight and appearance control behaviors, and body dissatisfaction and thereby improve population health in the United States.